Corneal Endotheliitis following Systemic West Nile Virus Infection. Issue 1 (2017) - Ferrari, Giulio; Dagna, Lorenzo; Ferretti, Francesca; Rama, Paolo
Background: We report the case of monolateral corneal endotheliitis, which occurred following systemic West Nile virus (WNV) infection. Methods: A 56-year-old male patient with right eye (RE) endotheliitis, diffuse arthralgias, and diagnosis of previous WNV systemic infection underwent a measurement of best spectacle corrected visual acuity (BSCVA), full ophthalmic examination, biomicroscopy, and in vivo scanning laser confocal microscopy (IVCM), before and after topical immunomodulatory treatment. In addition, a polymerase chain reaction test on aqueous humor was performed to test for WNV RNA sequences. Results: Photophobia was reported at presentation. A mild corneal haze was noted at the slit lamp exam. BSCVA in RE was 0.1 LogMar, corneal thickness was 667 micron, and confocal microscopy showed stromal folds. No WNV RNA sequences were detected in the aqueous humor. The cytomegalovirus and herpes virus were not tested as the patient refused additional procedures. One month after topical corticosteroid application in the RE, the patient reported significant improvement in photophobia, BSCVA improved to −0.1 LogMar, and corneal thickness was reduced to 540 microns. In addition, IVCM showed a disappearance of stromal folds. Conclusions: A presumptive diagnosis of WNV-associated endotheliitis was formulated. Improvement following topical corticosteroid treatment suggests an immune-based pathophysiology.